Superalloys 1992 (Seventh International Symposium) 1992
DOI: 10.7449/1992/superalloys_1992_447_456
|View full text |Cite
|
Sign up to set email alerts
|

Damage Tolerance of Alloy 718 Turbine Disc Material

Abstract: The influence of a modified heat treatment (MHT) and the standard heat treatment (SHT) on the microstructure and mechanical properties of Alloy 7 18 turbine disc material has been studied over a range of temperatures varying between room temperature and 650°C. The influence of these heat treatments has been studied on creep, low cycle fatigue (LCF), and fatigue crack growth rate (FCGR) properties. Test results have shown that the MHT improves the creep rupture life at 650°C but results in a loss of LCF crack i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…If we define the creep damage parameter as ω = A/πd 2 , and the rupture time is reached at ω = ω cr , then t r ∝ 1/ ss ε . The creep behaviour of wrought Alloy 718 with planar (the SHT material) and triangular-wave (the MHT material) grain boundaries at 650 °C under stress of 593 MPa were reported (Chang et al, 1992), as shown in Fig. 19.…”
Section: Creepmentioning
confidence: 99%
See 1 more Smart Citation
“…If we define the creep damage parameter as ω = A/πd 2 , and the rupture time is reached at ω = ω cr , then t r ∝ 1/ ss ε . The creep behaviour of wrought Alloy 718 with planar (the SHT material) and triangular-wave (the MHT material) grain boundaries at 650 °C under stress of 593 MPa were reported (Chang et al, 1992), as shown in Fig. 19.…”
Section: Creepmentioning
confidence: 99%
“…19. Creep curves for standard and damage tolerant microstructures of Alloy 718 (Chang et al 1992). Sessions et al (1977) studied the creep-oxidation interaction in Udimet 700.…”
Section: Creepmentioning
confidence: 99%
“…Working temperatures in aero-engines are higher and higher, the use of non-metallic sealing rings can not meet the requirements of the engine [1] . The use of metallic sealing ring instead of non-metallic sealing ring, can effectively solve the sealing problem under the high temperature and corrosion environment.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 Variable parameters of 1.7 Figure 2 Variable parameters of 2.6 part drawing (unit mm)part drawing (unit mm) We choose nickel-based superalloy GH4169 as the material of sealing ring[1,2] , working temperature can reach to 600 ℃. Under high temperature, the strength of the material is still very good, its oxidation resistance, fatigue, fracture toughness, plastic and other comprehensive performance are very good also, the basic mechanical properties parameters are shown in Table 1[3] .Table1Material mechanics parameter property…”
mentioning
confidence: 99%